Opciones de Manejo Basadas en el Clima para Productores de Ganado Vacuno en el Centro-Norte de Florida - Norman Breuer; Victor Cabrera; Peter E. Hildebrand; James W. Jones (EDIS)
AE468, a 9-page illustrated fact sheet by Norman Breuer, Víctor Cabrera, Peter E. Hildebrand, and James W. Jones, is the Spanish language version of CIR1476/AE289 Climate-Based Management Options for North Central Florida Beef Cattle Producers. It presents the results of a study interviewing ranchers and extension agents in North Central Florida, with an aim of developing user-friendly decision support systems for the agricultural production clientele. Includes references. Published by the UF Department of Agricultural and Biological Engineering, November 2010.